2016
DOI: 10.3390/jmse4040083
|View full text |Cite
|
Sign up to set email alerts
|

Procedure for Application-Oriented Optimisation of Marine Propellers

Abstract: The use of automated optimisation in engineering applications is emerging. In particular, nature inspired algorithms are frequently used because of their variability and robust application in constraints and multi-objective optimisation problems. The purpose of this paper is the comparison of four different algorithms and several optimisation strategies on a set of seven test propellers in realistic industrial design setting. The propellers are picked from real commercial projects and the manual final designs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Vesting et al conducted a detailed study of two propellers to improve their performance using PSO. The main constraint chosen in the design is cavitation nuisance [36]. Three PSO algorithms have been developed and applied on four commercial propellers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Vesting et al conducted a detailed study of two propellers to improve their performance using PSO. The main constraint chosen in the design is cavitation nuisance [36]. Three PSO algorithms have been developed and applied on four commercial propellers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Updated value is attained by the particle based on the local best, it has achieved in the previous iterations and global best value is the best value attained by the whole swarm. Velocity and position in design space are given in [36] as;…”
Section: Application Of Elitist Particle Swarm Optimizationmentioning
confidence: 99%
“…Kataria, Holder [10] suggested that technology mediated collaboration is very important for interdepartmental interactions, such as using shared displays to create better situational awareness. In today's context of EE, technologies have been mainly exploited in the manner of sensing complex environmental factors contributing to EE and automatically manipulating operational configurations for optimized performance [49][50][51]. They are not necessarily designed in a way to support the practitioners' awareness and assessment of EE performance or collaborative learning activities, which are considered crucial in energy saving activities [42,43,52].…”
Section: Tool Mediation and Interaction Designmentioning
confidence: 99%